Unravelling some Kinki earthworms (Annelida: Oligochaeta: Megadrili: Megascolecidae) - Part II - Blakemore, R.J. (Opuscula Zoologica Instituti Zoosystematici et Oecologici Universitatis Budapestinensis, 2010)
Metaphire tanbode sp. nov. is found in rice paddy in Kinki plain at Lake Biwa and Amynthas yamade sp. nov. isfrom Hira range to the West. M. tanbode belongs to the M. hilgendorfi / A. tokioensis species-complex, while montane A. yamadeis comparable to both Amynthas aeruginosus-group and Duplodicodrilus schmardae-group. Genetic barcoding (mtDNA COI) viatypes is attempted. Taxonomic ‘housekeeping’ requires replacement of invalid homonyms: e.g. Pheretima montana Ishizuka, 1999(non type-species P. montana Kinberg, 1867) is renamed Amynthas nonmontanus; others are A. nonsilvestris, A. noninvisus, A.nonmonticolus and A. nonsetosus, noms. et combs. novae. Thus Pheretima Kinberg, 1867 s. stricto remains unrecorded from Japanwhile prior Amynthas Kinberg, 1867, and its derivative Metaphire Sims & Easton, 1972, are abundant and diverse. Family andgeneric level definition and placement of Oriental pheretimoids are restated for the benefit of current workers and for novicefield-ecologists. Surveys of below-ground biodiversity of rice paddy in Lake Biwa is compared to more natural habitats aroundLake Pedder in Western Tasmanian Wilderness Area, and co-incidentally, both have 21 recorded earthworm species. Thus claimsfrom various countries of less than six species per location are contraindicated by thorough eco-taxonomic methods yieldingmore representative results.